EFFECT OF COMPRESSOR CARGO SUCTION PRESSURE AND TANK PRESSURE ON THE LENGTH OF THE RELIQUEFACTION PROCESS ON LPG/C GRIYA BORNEO - Bambang Sumali; April Gunawan; Larsen Barasa; Rika Desy Anggraini (Dinasti International Journal of Education Management And Social Science, 2021)
LPG / C Griya Borneo is a gas vessel with a semi-pressurized type, where the supporting components in the form of cargo handling equipment have a very big influence on the success and safety of ship operations. This is important to note because when the ship will carry out the loading process, the load temperature must be in accordance with the boiling point. High temperatures on ammonia loads can increase the pressure in the tank so that it exceeds the specified pressure limits and ammonia loads that have high temperatures need to be reliquefaction. In addition, the compressor compressor suction pressure that does not work in accordance with what is expected to affect the reliability process. This resulted in the reliquefaction process being longer than usual. The long reliquefaction process results in more fuel being used so that it costs a lot. Therefore the writer makes a thesis related to the problems experienced by the ship owned by PT Humpuss Transportasi Kimia aims to find out how much influence the compressor compressor suction pressure and tank pressure on the process of reliquefaction on the LPG / C Griya Borneo ship, the place where the authors practice.